2021
DOI: 10.1080/14737159.2021.1941880
|View full text |Cite
|
Sign up to set email alerts
|

Blood concentrations of proapoptotic sFas and antiapoptotic Bcl2 and COVID-19 patient mortality

Abstract: Background: There are no data on circulating concentrations of sFas (proapoptotic protein of extrinsic pathway) and Bcl2 (antiapoptotic protein of intrinsic pathway) in COVID-19 patients. Thus, our objective study was to determine whether an association exists between serum concentrations of sFas and Bcl2 and COVID-19 patient mortality. Methods: This observational and prospective study of COVID-19 patients was performed in eight Intensive Care Units (ICU) from Canary Islands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Lorente et al reported that soluble levels of sFas, a proapoptotic protein of the extrinsic pathway. were lower in patients who survived COVID-19 [38]. Interestingly, in line with our data, Cifaldi et al demonstrated that IL-6 directly reduced the expression of perforin and granzyme B [39].…”
Section: Discussionsupporting
confidence: 91%
“…Lorente et al reported that soluble levels of sFas, a proapoptotic protein of the extrinsic pathway. were lower in patients who survived COVID-19 [38]. Interestingly, in line with our data, Cifaldi et al demonstrated that IL-6 directly reduced the expression of perforin and granzyme B [39].…”
Section: Discussionsupporting
confidence: 91%
“…However, the bioactive chemicals must be separated and purified to study the exact mechanism of action [29,30]. Furthermore, increasing soluble Fas and B-cell CLL/lymphoma-2 (Bcl2) levels in COVID-19 patients raises the fatality rate in COVID-19 individuals [31]. However, Colpomenia sinuosa (C. sinuosa)-treated HCT-116 cells have downregulated antiapoptotic Bcl 2, which leads to caspases activation [32].…”
Section: Introductionmentioning
confidence: 99%
“…The ROS mediated activation of MAPK pathway also suppresses the BCL2 expression in the cells (Changchien et al, 2015). The decreased levels of BCL2 were observed in COVID-19 mortality cases than in COVID-19 survivors (Lorente et al, 2021). On the other hand, withaferin A pretreatment has shown the reversal of BCL2 downregulation in bromobenzene induced mice models accompanied by decrease in the levels of inflammatory cytokines TNFα and IL1β along with the restoration of antioxidant enzymes levels that were suppressed by bromobenzene (Vedi & Sabina, 2016).…”
Section: Discussionmentioning
confidence: 96%